Retrospective 6 month-outcomes and prognostic factors following spontaneous angiogram-negative non-perimesencephalic subarachnoid hemorrhage. (February 2022) - Kim, Myungsoo; Kim, Byoung-Joon; Son, Wonsoo; Kwak, Youngseok; Park, Jaechan; Park, Seong-Hyun; Kim, Yong-Sun; Kang, Dong-Hun
Highlights: SAH patients with non-PMH generally had uncomplicated clinical courses and favorable outcomes. Non-Fisher-type 3 pattern was a prognostic factor for favorable outcomes in the non-PMH. Long-term SAH was a prognostic factor for developing hydrocephalus in non-PMH. Abstract: Our objective was to analyze functional outcomes and prognostic factors in patients suffering from angiogram-negative non-perimesencephalic subarachnoid hemorrhage (non-PMH). In total, 1601 patients presenting with spontaneous SAH between January 2009 to December 2019 admitted to our institution were reviewed. Among them, 51 patients with angiogram negative non-perimesencephalic subarachnoid hemorrhage were analyzed. We divided patients into groups according to hemorrhage pattern and duration. Prognostic factors were assessed according to initial neurologic grade, early hydrocephalus, fisher grade, and duration of hemorrhage. Outcomes were assessed according to the modified Rankin Scale after 6 months. Overall, 41 patients (80.3%) with angiogram-negative non-PMH achieved a favorable outcome. In univariate analysis, good initial neurologic grade, absence of early hydrocephalus, non-Fisher-type 3 bleeding pattern, and short term hemorrhage (blood wash out <7 days after onset) duration were significantly associated with a favorable outcome. In multivariate analysis, a non-Fisher-type 3 hemorrhagic pattern (p < 0.05) and good initial neurologic state (p < 0.01) were independent predictors of favorable outcomes in angiogram-negative non-PMH patients. Patients with angiogram-negative non-PMH generally had favorable outcomes. A non-Fisher-type 3 hemorrhagic pattern and good initial neurologic state were prognostic factors of a favorable outcome in non-PMH. Furthermore, patients with long-term SAH were more likely to develop hydrocephalus. Evaluating the pattern and duration of subarachnoid hemorrhage may allow better prediction of outcomes in patients with angiogram negative and non-PMH.